الحوار المذهبي: مفهومه، ومنطلقاته، وضوابطه: Inter-Sectarian Dialogue: Its Concept, Foundations, and Conditions - الصلاحين, عبد المجيد محمود; داود, هايل عبد الحفيظ (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2014)
يهدف هذا البحث إلى بيان مفهوم الحوار المذهبي والأسس التي يبنى عليها، والضوابط التي تعين في تحقيق الغرض منه. فالحوار أمر حتمي بين مكونات الأمة المسلمة بمختلف مذاهبها العقدية أو الفقهية، وهو الأساس لأي حوار مع غيرها. ومن أجل أن يحقق الحوار المذهبي أهدافه لا بد أن ينطلق من مجموعة من المنطلقات وينضبط بعدد من الضوابط، ويأخذ بعدد من الأولويات. ويبين البحث أن المرجعية الأساسية في كل ذلك هو القرآن الكريم والسنة النبوية، فهما يؤكدان أن ما يجمع هذه الأمة أكثر بكثير مما يفرقها، ويشترطان أن يكون هدف الحوار هو الوصول إلى الحقيقة وليس الانتصار للمذهب بلا حقّ أو الباطل. This study aims to examine the concept of inter-sectarian dialogue among Muslims, and illustrate the foundations, conditions, and priorities of a successful dialogue. Dialogue among Muslims of various jurisprudential schools and doctrinal sects is inevitable, and is the foundation for any dialogue with others. In order to achieve its purposes, dialogue should stem from certain premises, controlled by certain conditions, and take a number of priorities. The study explains how the Holy Qur'an and Noble Sunnah constitute the frame of reference and the guiding authority for this dialogue, as they both affirm that which unites the Muslim Ummah together is much more than what divides it. This authority requires also that the objective of dialogue should be the search for the truth and not to defend a position, whether right or wrong.